Attitudes of Final-Year Medical Students in Jordan Towards Volunteering During a Pandemic - Alassaf A; Gharaibeh L; Alkubaisi F; Alkhawaldeh M; Dababseh S; Odeh R (Advances in Medical Education and Practice)
Abeer Alassaf,1 Lobna Gharaibeh,2 Fatima Alkubaisi,3 Majd Alkhawaldeh,3 Sohayla Dababseh,3 Rasha Odeh1 1Department of Pediatrics, The University of Jordan, Amman, Jordan; 2Pharmacological and Diagnostic Research Center, Faculty of Pharmacy, Al-Ahliyya Amman University, Amman, Jordan; 3School of Medicine, The University of Jordan, Amman, JordanCorrespondence: Abeer Alassaf, Department of Pediatrics, The University of Jordan, Queen Rania Street, Amman, 11942, Jordan, Tel +962 6 5353444 extn 2767, Fax +962 6 5356746, Email dr_abeerassaf@hotmail.comBackground: During COVID-19 pandemic in Jordan, a number of medical students participated in voluntary work. However, barriers and facilitators were unclear. Therefore, we aimed to evaluate their experience and attitudes towards volunteering during a pandemic and the factors affecting that.Methods: A cross-sectional questionnaire-based study, using paper and online questionnaire which were distributed to final-year medical students at the University of Jordan from August 2021 to October 2021, about their experience and attitudes towards voluntary work during pandemics.Results: A total of 375 of final year medical students responded to the questionnaire. The number of male and female respondents were equal. Past voluntary work experience prior to COVID-19 pandemic in 44.8% of students, while 79.2% of them did not volunteer during the COVID-19 pandemic. Around 60% of students were willing to participate in future voluntary work that does not involve patients infected with COVID-19, while 29.3% of them were willing to do so depending on the type of pandemic and the availability of vaccines. There were 86.1% of students who thought that participating in voluntary work involving infected patients during pandemics, should be optional; where 10.1% suggested that it should be compulsory if vaccines were available.Conclusion: The majority of medical students did not volunteer during the COVID 19 pandemic. However, many of them expressed willingness to take part in future pandemics. Providing sufficient protection aids and adequate training, would affect positively the willingness of medical students to participate in voluntary work during a pandemic.Keywords: volunteering, pandemic, medical students, Jordan